Antibiotic prescribing upon discharge from the hospital to long-term care facilities: Implications for antimicrobial stewardship requirements in post-acute settings. (9th November 2018) - Weber, Bo R.; Noble, Brie N.; Bearden, David T.; Crnich, Christopher J.; Ellingson, Katherine D.; McGregor, Jessina C.; Furuno, Jon P.
Abstract: Objective: To quantify the frequency and outcomes of receiving an antibiotic prescription upon discharge from the hospital to long-term care facilities (LTCFs). Design: Retrospective cohort study. Setting: A 576-bed, academic hospital in Portland, Oregon. Patients: Adult inpatients (≥18 years of age) discharged to an LTCF between January 1, 2012, and June 30, 2016. Methods: Our primary outcome was receiving a systemic antibiotic prescription upon discharge to an LTCF. We also quantified the association between receiving an antibiotic prescription and 30-day hospital readmission, 30-day emergency department (ED) visit, and Clostridium difficile infection (CDI) on a readmission or ED visit at the index facility within 60 days of discharge. Results: Among 6, 701 discharges to an LTCF, 22.9% were prescribed antibiotics upon discharge. The most prevalent antibiotic classes prescribed were cephalosporins (20.4%), fluoroquinolones (19.1%), and penicillins (16.7%). The medical records of ~82% of patients included a diagnosis code for a bacterial infection on the index admission. Among patients prescribed an antibiotic upon discharge, the incidence of 30-day hospital readmission to the index facility was 15.9%, the incidence of 30-day ED visit at the index facility was 11.0%, and the incidence of CDI on a readmission or ED visit within 60 days of discharge was 1.6%. Receiving an antibiotic prescription upon discharge was significantly associated with 30-day ED visits (adjusted odds ratio [aOR], 1.2; 95% confidence interval [CI], 1.02–1.5) and with CDI within 60 days (aOR, 1.7; 95% CI, 1.02–2.8) but not with 30-day readmissions (aOR, 1.01; 95% CI, 0.9–1.2). Conclusions: Antibiotics were frequently prescribed upon discharge to LTCFs, which may be associated with increased risk of poor outcomes post discharge.